2012
DOI: 10.1097/mph.0b013e31822bf699
|View full text |Cite
|
Sign up to set email alerts
|

A Marked Decrease in CD4-positive Lymphocytes at the Onset of Hepatitis in a Patient With Hepatitis-associated Aplastic Anemia

Abstract: A 10-year-old Japanese boy developed acute hepatitis with high levels of serum Torque teno virus DNA and marked lymphocytopenia, especially CD4 T-lymphocytopenia. Although the total lymphocyte counts rose as the patient recovered from hepatitis, this was largely because of a marked rise in CD8 cells. In contrast, CD4 cells recovered poorly, resulting in a further striking fall in the CD4/8 ratio. Two months later, the patient developed hepatitis-associated aplastic anemia. He was successfully treated with immu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
11
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 19 publications
5
11
0
Order By: Relevance
“…With recovery from HAAA, the T-cell repertoire could return to normal. Ikeda et al [14] demonstrated a marked decrease in CD4+ lymphocytes in a patient with HAAA, and in the current study, we found that HAAA patients had a lower ratio of CD4+/CD8+ T cells compared with non-HASAA. Furthermore, we found that in HAAA patients, the serum Th1 cytokines, IL-2 and TNF-α, were at higher levels than in non-HASAA patients.…”
Section: Discussionsupporting
confidence: 78%
“…With recovery from HAAA, the T-cell repertoire could return to normal. Ikeda et al [14] demonstrated a marked decrease in CD4+ lymphocytes in a patient with HAAA, and in the current study, we found that HAAA patients had a lower ratio of CD4+/CD8+ T cells compared with non-HASAA. Furthermore, we found that in HAAA patients, the serum Th1 cytokines, IL-2 and TNF-α, were at higher levels than in non-HASAA patients.…”
Section: Discussionsupporting
confidence: 78%
“…The same findings have also been reported in transplant patients with chronic hepatitis E [57] and in the liver parenchyma after HEV-induced acute liver failure [56]. Other authors have also observed lymphopenia in patients with hepatitis-virus-associated aplastic anaemia (HAA), suggesting that HAA may be influenced by the immune-mediated destruction of bone marrow [58]. Several viruses are considered to be triggers for autoimmunity and overt autoimmune disease.…”
Section: Discussionsupporting
confidence: 66%
“…Furthermore, this study suggests that a number of different immunosuppressive therapies may be effective at reducing CD8 + inflammation, and further research is indicated to determine optimal therapy for these patients. We found that all 3 iPALF patients in our study who developed AA and had peripheral blood flow cytometry available had a decreased CD4:CD8 ratio (due to an increase in CD8 cells), and this finding has been reported in other studies of hepatitis‐associated AA . In McKenzie et al, all iPALF and acute hepatitis patients had a low CD4:CD8 ratio by peripheral blood flow cytometry, 3 of whom developed AA .…”
Section: Discussionmentioning
confidence: 99%
“…We found that all 3 iPALF patients in our study who developed AA and had peripheral blood flow cytometry available had a decreased CD4:CD8 ratio (due to an increase in CD8 cells), and this finding has been reported in other studies of hepatitis-associated AA. (24,25) In McKenzie et al, all iPALF and acute hepatitis patients had a low CD4:CD8 ratio by peripheral blood flow cytometry, 3 of whom developed AA. (8) We propose that a low CD4:CD8 ratio is an additional biomarker of the iPALF immune dysregulation phenotype as well as of those iPALF patients who are more likely to develop AA.…”
Section: Discussionmentioning
confidence: 99%